Molecular hydrogen emission in the interstellar medium of the Large Magellanic Cloud. Issue 3 (28th November 2014) - Naslim, N; Kemper, F; Madden, S C; Hony, S; Chu, Y -H; Galliano, F; Bot, C; Yang, Y; Seok, J; Oliveira, J M; van Loon, J Th; Meixner, M; et al.
Abstract: We present the detection and analysis of molecular hydrogen emission towards ten interstellar regions in the Large Magellanic Cloud. We examined low-resolution infrared spectral maps of 12 regions obtained with the Spitzer infrared spectrograph (IRS). The pure rotational 0–0 transitions of H2 at 28.2 and 17.1 μm are detected in the IRS spectra for 10 regions. The higher level transitions are mostly upper limit measurements except for three regions, where a 3σ detection threshold is achieved for lines at 12.2 and 8.6 μm. The excitation diagrams of the detected H2 transitions are used to determine the warm H2 gas column density and temperature. The single-temperature fits through the lower transition lines give temperatures in the range 86–137 K. The bulk of the excited H2 gas is found at these temperatures and contributes ∼5–17 per cent to the total gas mass. We find a tight correlation of the H2 surface brightness with polycyclic aromatic hydrocarbon and total infrared emission, which is a clear indication of photoelectric heating in photodissociation regions. We find the excitation of H2 by this process is equally efficient in both atomic- and molecular-dominated regions. We also present the correlation of the warm H2 physical conditions with dust properties. The warm H2 mass fraction and excitation temperature show positive correlations with the average starlight intensity, again supporting H2 excitation in photodissociation regions.